P203 Social complexity remains a challenge for the provision of TB care. (12th November 2019) - Abunga, YO; Davies, R; Molefe, T; Faccenda, J; Brij, SO
Abstract : Introduction: There has been a local increase in TB hospital admissions with some cases requiring lengthy in-patient stays. Treatment for medically complex and/or drug resistant TB is associated with significant cost implications and increased length of stay (LOS). In comparison, socially complex TB cases (homelessness; drug and alcohol dependence; imprisonment; non-compliance; denial of TB diagnosis) often require protracted period of admission. Aim: To determine factors affecting hospital length of stay (LOS), a retrospective survey was undertaken looking at adult patients admitted with a primary diagnosis of TB between 2012 and 2019. Methodology: All adult TB patients admitted between 01/01/2012 and 01/06/2019 were included. Clinical notes were used to obtain clinical history, LOS and demographicinformation. Results: 71 TB admission episodes were identified in 62 patients (male gender 61%; median age 43 years; range 18–94 years): 56 patients with a single admission; 5 with 2 admissions; 1 with 5 admissions. Overall, median adjusted LOS 15 days (range 1–134). Non-complex admissions independent of disease severity (including 4 TB drug side-effects and 10 drug resistant TB) accounted for 54 episodes with median LOS 11 days (range 1–127). Complex social admissions accounted for 17 episodes with median LOS 50 days (range 3–134). Factors affecting admission/discharge included homelessness 12; compliance 5; alcohol and drug-dependence 4; imprisonment 3. More than 1 social factor was present in 8 episodes. There were 22 episodes with LOS >31 days and complex social admissions (n=12) appeared to be significantly associated with extended length of stay RR 5.34; 95% CI 2.14 to 13.33; p 0.0003. Conclusion: Length of hospital stay is significantly extended by social complexity. Homeless patients accounted for 70% of complex social admissions. Lack of recourse to public funds remains an on-going issue despite locally agreed arrangements for provision of housing for the duration of TB treatment but this is still subject to a relatively lengthy process, creating unnecessary delay. In addition, if patients with pulmonary TB (and social complexity) are persistently smear positive, a negative culture for discharge is recommended, thereby increasing LOS.